A strategy towards the synthesis of superhydrophobic/superoleophilic non-fluorinated polypyrrole nanotubes for oil–water separation. Issue 56 (11th September 2020) - Jha, Purushottam; Koiry, Shankar P.; Sridevi, C.; Putta, Veerender; Gupta, Deeksha; Chauhan, Anil K.
Abstract : Superhydrophobic and superoleophilic polypyrrole nanotubes for oil–water separation. Abstract : Superhydrophobic/superoleophilic materials have shown great potential for applications in oil/water separation. However, practical applications of these materials are restricted due to their toxicity and complicated, expensive, and non-eco-friendly fabrication procedures. Here, we have successfully developed an easy, simple, cost-effective, and environmentally friendly strategy towards the synthesis of superhydrophobic and superoleophilic porous polypyrrole nanotubes. Such wettability has been introduced into polypyrrole by co-doping with sodium dodecylbenzenesulfonate, a surfactant for lowering surface energy and controlling the morphology of the nanotubes. These non toxic and environment friendly polymer nanotubes exhibit oil absorption capability from oil/water mixtures with a reasonable efficiency with good reusability.